Study of Development Planning and Development Agrosilvopastoral for the Improvement of Village Economy in West Sumatra: (Case of Sumanik Village in Tanah Datar District) - Indira Adnani, Rudi Febriamansyah, Novirman Jamarun, Ricky Avenzora (Universitas Andalas, 2018)
West Sumatera has a cultivated area of 2,340,111,73 ha, that is a very potential land for the development of the agricultural sector: Food crops, woody plants, and livestock. The purpose of this research is to analyze perception, motivation, and readiness of farmer community of Sumanik Village to agrosilvopastura. As well as their preferences in choosing agricultural systems, to know the potential and existing problems in Sumanik Village to support agrosilvopastura, to analyze the impact of Agrosilvopastoral activities on the economics of Village farmers community in Sumanik ; And elaborate the most appropriate Agrosilvopastoral model that was applied in Sumanik Village while maintaining ecological, social and economic sustainability. The research was conducted in Sumanik Village in Tanah Datar District with descriptive method. Survey in February 2015 to December 2016, The results showed that the farmers of respondents in Sumanik village, positively perceptive to agrosilvpastura farming system, and motivated to do Agrosilvopastoral farming system, they tend to do Agrosilvopastoral in demonstration plot for learning.There are two problems in Sumanik Village, the first area of Sumanik is a dry area, so the right technology to develop the farm is needed. The second problem is, the communities in Sumanik do not have the capital to buy cattle. The result of financial analysis that was done was Agrosilvopastoral farming system have positive impact to farmer community economics in Sumanik Village which showed by business feasibility that is run NPV value Rp 92,193.13, IRR value 39,94%, ROI value 39.94, RC ratio 1.82, PBP 2.13 year, BEP every year is 9 head of cattle. From the research result formulated that Agrosilvopastoral model that most appropriately applied in Sumanik Village is in the form of Agrosilvopastoral communal farm.